T-type Ca2+ channels and absence epilepsy - Shin, Hee-Sup (ELSEVIER SCI LTD, 2006)
Burst firing of the thalamic neurons is driven by the low threshold Ca2+ spike generated by Ca2+ influx through T-type Ca2+ channels when these channels are activated by membrane hyperpolarization due to inhibitory inputs. The major inhibitory inputs to the thalamocortical (TC) neurons are from the GABAergic neurons in the thalamic reticular nucleus. Thalamic burst firings have long been implicated in the pathogenesis of absence epilepsy. The recent progress in genetic approaches has provided with an opportunity to examine this issue at the level of an organism. In this review I describe results primarily obtained from the analysis of the mice deficient for the alpha 1G locus which is the predominant gene underlying the low threshold Ca2+ currents in the TC neurons. Current results so far demonstrate the essential role of the thalamocortical bursts in certain forms of absence seizures. Understanding of the pathophysiological mechanisms of absence epilepsy may help develop drugs to control the disease. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: VOLTAGE-ACTIVATED CURRENTS; CALCIUM-CHANNEL; THALAMIC NEURONS; MICE LACKING; SPIKE-WAVE; RELAY NEURONS; MUTANT MOUSE; SEIZURES; ETHOSUXIMIDE; MUTATIONS